Analisis Pengaruh Kualitas Pelayanan terhadap Niat Berkunjung Ulang Pasien dengan Kepuasan Pasien sebagai Variabel Intervening di Unit Pelayanan Rawat Jalan Rumah Sakit Siaga Raya Tahun 2018 (Journal of Hospital Management, 2019)
Problems that are often encountered in hospital outpatient care units are ups and downs of intention patient to visit again, this is caused by the poor quality of services in outpatient units that can indirectly interfere with the level of patient satisfaction with these services and ultimately affect the intention patient to visit again. This study aims to determine the factors that influence the quality of care for the intention patient to visit again with patient satisfaction as an intervening variable in the outpatient service unit. This study uses a quantitative approach, survey method and causative technique type testing hypotheses with Structural Equation Modeling (SEM) analysis techniques with a sample of 178 respondents. The results showed that the quality of care significantly affected the intention to revisit patients. It was also evaluated with patient satisfaction also significantly affecting intention patient to visit again. These results can be the basis for hospital management in improving the quality of services to achieve high patient satisfaction and intention patient to visit again. Keyword: Service Quality; Intention patient to visit again; Patient Satisfaction